Analysis Of Service Quality, Food Quality, Atmosphere Against Revisit Intention and Positive Word Of Mouth at Casual Dining Restaurant in Batam City - Ho Gefi Lee; Renny Christiarini (Komunitas Dosen Indonesia, 2021)
The purpose of this study is to analysis the impact of three elements of service quality dimensions (reliability, responsiveness and tangible), food quality and atmosphere on satisfaction, and to analysis if customer satisfaction have an impact to customer revisit intention and positive word of mouth. Data were collected from customers who had visited casual dining restaurants in Batam city through a self-administered questionnaire. Research questionnaires were distributed by researchers via google form, and have collected 359 (three hundred and fifty-nine) respondent data. This study shows that the three dimensions of service quality and food quality were significant to customer satisfaction. Also, the customer satisfaction were significant to positive word of mouth. But this study also shows that atmosphere was found not significant to customer satisfaction, and customer satisfaction not significant to revisit intention. This research conjectured that factors that influence the customers to be more satisfaction and do revisit to the casual dining restaurant are worthy of repeat research because of the decrease COVID-19 cases in batam city.